A Numerical Study Of Oscillating Sub-Boundary Layer Vortex Generators Application - Zulkefli, Nur Faraihan (2011)

(untitled)
A numerical simulation for oscillating sub-boundary layer vortex generator (SBVG) with Co-rotating (Co) and Counter-Rotating (Co-R) configurations was carried out. The device was attached and tested on a flat plate with zero- pressure gradient condition. This three-dimensional (3D) simulation adopted a fully turbulent flow, having a Reynolds number of 1x106. The Reynolds-averaged Navier-Stokes (RANS) equations with the SST k- turbulence model were used to predict the flow field which employed hybrid mesh. The SBVG was oscillated in a sinusoidal motion between 180 and -180. The results show that the profile for Counter-Rotating (Co-R) SBVG was more dominant due to its strong vortices compared to co-rotating.